Oat se man dikhta hai - Chintan, Shubh (Chennai Nation Press, 2020)
This book is a small collection of 50 poems .These poems depict all kinds of Human emotions, desires and imaginations. It could have been made bigger but it was considered appropriate to limit it to 50 poems only underlining the philosophy that small should reflect big. In human life also, we are taught that what should be written or said should be few words but what it could convey should be much more.
Keywords: Kavita sangrah